Analisis Beban Kerja Mental Driver ShopeeFood di Kota Surakarta Menggunakan Metode NASA-TLX - Muhamad Ramdan Gimnastiar (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Digital economic transformation has expanded platform-based work, yet the flexibility of food-delivery work is accompanied by cognitive, temporal, and emotional demands. This study analyzes the mental workload of ShopeeFood drivers in Surakarta, identifies the dominant NASA-TLX dimension, and formulates improvement recommendations. A quantitative descriptive study was conducted from March to July 2026 with 100 active drivers selected through purposive sampling; the minimum sample was determined using the Lemeshow formula. Data were collected using the NASA-TLX questionnaire and processed in Microsoft Excel. The mean Weighted Workload (WWL) score was 73.22, indicating a high workload; 93% of respondents were classified as high and 7% as very high. Temporal Demand contributed the most (19.17%), followed by Frustration Level (18.72%) and Mental Demand (18.08%). Recommendations emphasize regular breaks, work-duration control, route planning, emotional regulation, daily targets, and routine checks of driver and vehicle condition.